ANALYSIS OF THE EFFECT OF PRICE PERCEPTION, PRODUCT QUALITY, PHYSICAL EVIDENCE ON CONSUMER SATISFACTION AND PURCHASE DECISION ON THE SUMBER JAYA LIVESTOCK GROUP - Kharisma Bintang Eka Putera; Nanis Susanti; IB Cempena (International Journal Labs, 2022)
The purpose of this study was to examine the effect of price perception, product quality, physical evidence, on consumer satisfaction and purchasing decisions as intervening variables. With a sample of 60 out of 70 customers in the Sumber Jaya livestock group using the slovin technique and participating in this study. Data were collected in 2021 using a questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study prove that price perception, product quality, physical evidence, have a significant effect on purchasing decisions. price perception has a significant effect on Consumer Satisfaction. Meanwhile, product quality and physical evidence have no significant effect on Consumer Satisfaction. And purchasing decisions have a significant effect on Consumer Satisfaction. This finding reminds empirical evidence that it is very important to always pay attention to customer behavior which is useful for the key to innovation so that customers do not hesitate in making purchasing decisions at the Sumber Jaya Livestock Group.